+0  
 
0
246
4
avatar+230 

Prove this :  

If \(a^{3}+b^{3}=2\) then \(a+b\leq 2\)

ant101  Apr 2, 2017
Sort: 

4+0 Answers

 #1
avatar
0

One simple proof is when:

a=1 and b=1 !!.

Guest Apr 2, 2017
 #2
avatar+1508 
0

Nice one guest.

MysticalJaycat  Apr 2, 2017
 #3
avatar+79 
0

good gest. vry nic.

mathtoo  Apr 2, 2017
 #4
avatar+310 
+1

Lets assume a+b>2

 

a>2-b

Therefore,

 

a3>(2-b)3=8-b3+6b2-12b

 

We know a3=2-b3 (because a3+b3=2)

 

2-b3>8-b3+6b2-12b ........add (b3-2)------>

0>6+6b2-12b..........divide by 6----------->

0>1+b2-2b=(b-1)2

but (b-1)2 cant be smaller than 0!

 

we could also find the smallest number that is bigger than a+b if we called 2 'c1' and the limit for the largest number 'c2' to get a more general solution for every c1.

 

a3+b3=c1

 

a3=c1-b3

 

we want to find the smallest c2 that is bigger than or equals to a+b. (a+b<=c2)

 

a<=c2-b -------->

 

a3<=c23-b3+3b2*c2-3b*c22 ---------->

 

c1-b3<=c23-b3+3b2*c2-3b*c22 --------->

 

0<=c23-c1+3b2*c2-3b*c22=3c2*[(b-(c2/2))2+c22/3-c1/c2*3-c22/4]

 

so now there are 3 options-

 

1. c2 is negative, therefore we want [(b-(c2/2))2+c22/3-c1/c2*3-c22/4] to always be negative (because negative*negative=positive) but we cant because b can be as big as we want. meaning we cant do that.

 

2. c2=0, meaning c1=0. but cis a constant that cant be determined by c2.

 

3. c2 is a positive number, meaning we want [(b-(c2/2))2+c22/3-c1/c2*3-c22/4] to be positive always (because positive*positive=positive)

 

we know the minimum value for (b-(c2/2)) is 0. so we need c22/3-c1/c2*3-c22/4 to be bigger than 0.

 

c22/3-c1/c2*3-c22/4=c22/12-c1/c2*3>=0 multiply by 3*c2-------------->

 

c23*1/4-c1>=0

 

therefore, c2>=(c1*4)1/3 

 

 

we can also use calculus for this question

 

a=x, b=(c1-x3)1/3

 

f(x)=x+(c1-x3)1/3

f'(x)=1-3*x2/3*(c1-x3)1/3-1=1-x2(c1-x3)-2/3=0 ----------------->

 

x2(c1-x3)-2/3=1 multiply by (c1-x3)2/3 -------------------->

 

x2=(c1-x3)2/3---------------------->

 

x6=(c1-x3)2=c12+x6-2*c1*x3------------------>

 

2*c1*x3=c12 divide by (c1*2) ------------->

 

x=(c1/2)1/3

 

f((c1/2)1/3)=(c1/2)1/3+(c1-c1/2)1/3=2*(c1/2)1/3. this is a more accurate answer for the maximum value of a+b.

Ehrlich  Apr 2, 2017
edited by Ehrlich  Apr 3, 2017

18 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details